O erro no ensino de Matemática: reflexões a respeito de ações docentes no processo de ensino - Sousa, Valdirene da Silva de (2017)
The present study has started on the will to investigate the ways teachers on elementary levels, while teaching Math, deal with situations when students make errors when performing tasks. Seeing that, it was built the following question: which characteristics can be identified in the teacher’s speech about their practice in using the error as a resource for learning? It was expected with this question to identify convergences and/or divergences among theoretical instances and teacher’s reports about their practices. The theoretical support was found specially on the ideas of Cury and Brousseau in order to analyze the assumptions teachers have on students errors. In order to focus on teacher’s views we added to the consideration teacher’s backgrounds and the error and obstacles concept, aiming to narrow the ideas adopted although the research. A qualitative approach or research was chosen in which six people took part, all elementary teachers of 4th and 5th grades from private and public schools in the city of São Paulo. The data were collected through semi-structured questionnaires. As a result of this process of reflection, we can infer that teachers use student’s errors in their Math classes in different possibilities inherent to the teaching process. As strategies, the teachers affirmed to use, in most cases, collective corrections in which the students participate by showing their reasoning in carrying out the activities, sometimes going to the blackboard to register them, or participating orally. Teachers have stated that they rarely use individualized correction because there is not enough time to realize this dynamic. All of them ask students to erase the resolution when they miss an activity, and to redo copying from the blackboard. It is expected from this paper to contribute to the thinking of errors students make as part of what they understand of what is taught